Edukasi Pengolahan Sampah Rumah Tangga pada Ibu PKK di Dusun Kedon Boyolali - Raisya Najwa Herlintang; Salsabila Nafisah; Rasyiid Abdul Aziz; Windi Wulandari (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
Waste remains a serious environmental issue in Kedon Village, Boyolali Regency, due to a suboptimal management system and reliance on landfills (TPA). This community service activity aims to improve the knowledge and skills of 21 partners, specifically women from the Family Welfare Movement (PKK), in household waste management. The activity involved socialization and training on ecobrick and compost making. Evaluation used pre- and post-test questionnaires to measure the effectiveness of the intervention. Results showed an increase in knowledge from an average of 74.2% to 82.6% and in skills from an average of 55.85% to 80.4%, as well as high enthusiasm from partners in participating in all activities. Through this empowerment, the intervention has proven effective in addressing household waste issues, and is expected to create a cleaner and healthier village environment.